2011
DOI: 10.1109/tac.2010.2088631
|View full text |Cite
|
Sign up to set email alerts
|

Approximate Moment Dynamics for Chemically Reacting Systems

Abstract: In the stochastic formulation of chemical kinetics, the differential equation that describes the time evolution of the lower-order statistical moments for the number of molecules of the different species involved, is generally not closed, in the sense that the right-hand side of this equation depends on higher-order moments. Recent work has proposed a moment closure technique based on derivative-matching, which closes the moment equations by approximating higher-order moments as nonlinear functions of lower-or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
236
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 224 publications
(240 citation statements)
references
References 19 publications
4
236
0
Order By: Relevance
“…45 Often solutions of the equilibrium RRE corresponding to the asymptotic VFP will suffice, 47 although more sophisticated moment closure approximations for the asymptotic VFP will usually be more accurate. 48,49 In some circumstances it may be easier to estimate the required averages by making brief SSA runs of the VFP. 50 A software implementation of the ssSSA which automatically and adaptively partitions the system and efficiently computes the modified slow propensity functions for general mass action models is available.…”
mentioning
confidence: 99%
“…45 Often solutions of the equilibrium RRE corresponding to the asymptotic VFP will suffice, 47 although more sophisticated moment closure approximations for the asymptotic VFP will usually be more accurate. 48,49 In some circumstances it may be easier to estimate the required averages by making brief SSA runs of the VFP. 50 A software implementation of the ssSSA which automatically and adaptively partitions the system and efficiently computes the modified slow propensity functions for general mass action models is available.…”
mentioning
confidence: 99%
“…There have been numerous attempts to define F, either by assuming an underlying distribution (12,15,16) or through numerical approximation (17)(18)(19). However, closure schemes thus far exhibit limited accuracy and uncertain utility.…”
mentioning
confidence: 99%
“…Azunre et al 39 showed that for very small molecule numbers, using only two moments can lead to unstable results. Singh and Hespanha 16 developed a derivative-matching approach in the context of polynomial rate equations, which proved to work very well in particular for small molecule numbers. For the examples described in this paper, the proposed method shows differences in behaviour for very low molecule numbers.…”
Section: Discussionmentioning
confidence: 99%